PETA KAJIAN MANAJEMEN PENDIDIKAN DI INDONESIA - Fetty Ernawati; Muhammad Munadi (Universitas Negeri Malang, 2021)
Abstract: This study aims to map educational management studies in Indonesia, which includes the mapping of educational management studies in state and private colleges; as well as the comparison between the number of scientific journals and the number of educational management study programs from all levels of higher education in Indonesia. This study employed quantitative research methods and its data sources were originated from documents available on the website of Sinta Kemenristek/BRIN. The data were analyzed by employing descriptive statistics and explained by using descriptive narrations. The results show that there are 48 subjects of educational management studies in Indonesia and there are 299 authors who conduct studies on these subjects. These studies were published by 24 scientific journals. The subjects of educational management and Islamic educational management studies have the most sub-studies compared to other study subjects, including 12 sub-studies offered by these scientific journals. Moreover, there are 7 scientific journals owned by private Islamic colleges, 6 scientific journals owned by state colleges, 2 scientific journals owned by private colleges, and 1 scientific journals owned by a scientific community. Keywords: Educational management; mapping scientific journals Abstrak: Penelitian ini bertujuan untuk memetakan kajian manajemen pendidikan di Indonesia, yang mencakup pemetaan kajian manajemen pendidikan di PTN dan PTS; serta perbandingan antara jumlah jurnal dengan jumlah program studi manajemen pendidikan dari semua jenjang pendidikan di Indonesia. Penelitian ini menggunakan metode penelitian kuantitatif dengan sumber data dari dokumen di website sinta Kemenristek/BRIN. Analisis data menggunakan statistik deskriptif, dan dijelaskan dengan menggunakan kualitatif deskriptif. Hasil penelitian menunjukkan subyek kajian manajemen pendidikan di Indonesia tercatat sejumlah 48 dan terdapat 299 orang penulis yang mengkajinya. Terwadahi dalam jurnal yang berjumlah 24 jurnal. Subyek kajian Education Management/Islamic Education Management juga paling banyak memiliki sub kajian dibandingkan subyek kajian lainnya yaitu memiliki 12 sub kajian yang ditawarkan oleh jurnal. Jurnal terbanyak dimiliki oleh PTKIN yaitu 8 jurnal dan PTKIS dengan 7 jurnal, selebihnya 6 jurnal dari PTN, 2 jurnal dari PTS dan 1 jurnal dari komunitas keilmuan. Kata kunci: Peta kajian jurnal; manajemen pendidikan